Resilience processes among Ukrainian youth preparing to build resilience with peers during the Ukraine-Russia war - Giordano, Francesca; Lipscomb, Shannon; Jefferies, Philip; Kwon, Kyong-Ah; Giammarchi, Marianna (Frontiers in Psychology, 2024)
The war in Ukraine significantly impacts the mental health and well-being of its youth. Like other communities affected by war, Ukraine’s youth are at risk of developing psychopathological symptoms, and there is a shortage of mental health and psychosocial support services to address this. Resilience-building initiatives present an alternative approach to supporting the well-being of young people by promoting protective processes to enhance the likelihood of positive development in the context of adversity. Emerging research findings suggest that young people themselves can serve as powerful facilitators of such initiatives with one another. Yet, evidence about culturally and contextually relevant protective processes is needed to guide such interventions, especially among young people experiencing the war and working to boost resilience within their communities. In this study, we identified key protective processes Ukrainian youth depend on as they adapt to the conflict while also preparing to implement a resilience-building intervention as a facilitator. Through thematic analysis of transcripts of three training sessions with Ukrainian youth (n = 15, 100% female; aged 18–22), we identified the following themes: positive thinking, sense of control, emotion awareness and regulation, close personal relationships, and community support. Findings also highlighted the cultural and contextual nuance of these protective processes, as well as individual differences in the ways they co-occurred and manifested within each youth. Results have implications for developing tailored yet flexible resilience-building interventions that can be delivered by lay people, including youth with their peers, in Ukraine and other cultures and contexts.